X-ray absorption fine structure studies of buried Ge-Si interfaces - Aebi, Philipp; Tyliszczak, T.; Hitchcock, A. P.; Jackman, T. E.; Baribeau, J.-M. (My University, 1991)
We have used Ge A-edge x-ray absorption fine structure (EXAFS) and a gas ionization detector with sample rotation to study the local environment of nominally pure Qe layers buried in single crystal Si. The samples were grown by molecular-beam epitaxy on Si( 100). The dependence on thickness, number of Ge layers and growth temperature is explored. Considerable sensitivity to the quality of the epitaxial growth is observed. For instance the degree of mixing of the Si and Ge layers is a function of the growth temperature. A weak polarization dependence of the Ge K-edge. EXAFS is observed. The initial quantitative analysis provides estimates of intermixing in the thinnest layers which are compatible with results of complementary Raman measurements.